MC68HC11 microcontroller based universal memory programmer - Ong, Kian Chun (2010)
Memory product is an essential component for all microcontroller and microprocessor system. The high demand towards memory product has tremendously promoted the development of various types of memory product in the market such as the EPROM, EEPROM, and NVRAM. All these memory products require a programming stage in order to be used in the microprocessor and microcontroller system. The programming stage involves the storage of object file codes onto the memory devices using a memory programmer and these codes can be retrieved and read by the microprocessor and microcontroller during its operation. Therefore, memory programmer is a crucially important device for all microprocessor and microcontroller users. However, most memory programmers are limited to program non volatile ROM such as PROM, EPROM and EEPROM only. Thus, NVRAM users need to develop their own programming coding to program NVRAM. This, undoubtedly, is a setback to potential NVRAM users. For this reason, a universal memory programmer is designed to support various types of memory products including the fast emerging NVRAM. In addition, the programmer can support various object file loading to support a wide range of microprocessor system available in the market. As a result, the MC68HC11 microcontroller based universal memory programmer (UMP11) can provide an all-in-one solution to the users for the programming of their memory products.